2015
DOI: 10.17583/redimat.2015.1517
|View full text |Cite
|
Sign up to set email alerts
|

School Socio-Cultural Identity and Perceived Parental Involvement About Mathematics Learning in Greece

Abstract: In this quantitative study we investigated the primary school students’ perceived parental involvement in mathematics with respect to different school socio-cultural identity as identified by the students’ ethnicity. 493 students attending the two last grades of three primary schools participated in the study. The role of the students’ grade and gender, as well as the mother/father contrast were also considered in the analyses. The findings of the study revealed both inter-school and intra-school divergences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…According to our results, the students of group A seem to agree mostly with their fathers and the students of group B with their mothers. This finding is interesting as we have found that the perceived parental involvement qualitatively differs between the mother and the father about mathematics, as the children's perception of their father's role is connected with a wider range of mathematical practices (including checking homework frequently, asking about assessment results, encouragement) (Moutsios-Rentzos et al, 2015). Furthermore, the majority of the students seemed to appreciate the effectiveness of their mothers' and fathers' help.…”
Section: Child-parent Collaboration For Homeworkmentioning
confidence: 79%
See 4 more Smart Citations
“…According to our results, the students of group A seem to agree mostly with their fathers and the students of group B with their mothers. This finding is interesting as we have found that the perceived parental involvement qualitatively differs between the mother and the father about mathematics, as the children's perception of their father's role is connected with a wider range of mathematical practices (including checking homework frequently, asking about assessment results, encouragement) (Moutsios-Rentzos et al, 2015). Furthermore, the majority of the students seemed to appreciate the effectiveness of their mothers' and fathers' help.…”
Section: Child-parent Collaboration For Homeworkmentioning
confidence: 79%
“…Our approach was based on six axes: a) mathematics attainment, b) a dynamic affect system including attitudes, beliefs about the nature of mathematics, values and selfconfidence, and c) child-parent collaboration for homework. We conducted our investigations including the differentiation between father and mother, as supported by the family structure and function in Greece and the related research findings (Moutsios-Rentzos et al, 2015). We posited that these findings would help us to clarify what aspects of parental involvement are crucial for the construction of the children's identity in mathematics in order to discuss ways of supporting them.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 92%
See 3 more Smart Citations